Learning-from-parents: exploitative knowledge acquisition and the innovation performance of joint venture - Chen, Chung-Jen; Lin, Bou-Wen; Lin, Jun-You; Hsiao, Yung-Chang (The Journal of technology transfer, 2020)
This article examines the effects of joint venture’s exploitative knowledge acquisition on its innovation performance under the contexts of joint venture-parent similarity in technology, industry and country. We suggest that there is an inverse U-shaped relationship between joint venture’s exploitative knowledge acquisition and innovation performance. Moreover, the moderating role of joint venture-parent similarity in technology and country are recognized and are hypothesized as positively moderate the effect of exploitative knowledge acquisition on innovation performance, but industrial similarity is recognized and hypothesized as negative moderator. Negative binomial regression was used to test the hypotheses in a panel data of 183 joint venture cases and the findings support our prediction. The results of this study can help reconciling contradictory findings from previous studies by demonstrating the potential impact of exploitative knowledge acquisition on innovation performance.